Nkx6.1 is essential for maintaining the functional state of pancreatic beta cells - Taylor, Brandon L. (2013)
Recently, loss of beta cell-specific traits has been proposed as an early cause of beta cell failure in diabetes. However, the molecular mechanisms that underlie this loss of beta cell features remain unclear. Here, we identify an Nkx6.1-controlled gene regulatory network as essential for maintaining the functional and molecular traits of mature beta cells. Conditional Nkx6.1 inactivation in adult mice caused rapid-onset diabetes and hypoinsulinemia. Genome-wide analysis of Nkx6.1-regulated genes and functional assays further revealed a critical role for Nkx6.1 in the control of insulin biosynthesis, insulin secretion and beta cell proliferation. Over time, Nkx6.1-deficient beta cells acquired molecular characteristics of delta cells, revealing a molecular link between impaired beta cell functional properties and loss of cell identity. Given that Nkx6.1 levels are reduced in human type 2-diabetic beta cells, our study lends support to the concept that loss of beta cell features could contribute to the pathogenesis of diabetes.